Smoking and attention in schizophrenia spectrum disorders: What are we neglecting? - Keřková, Barbora; Knížková, Karolína; Siroňová, Aneta; Hrubý, Aleš; Večeřová, Monika; Šustová, Petra; Jonáš, Juraj; Rodriguez, Mabel (Frontiers in Psychology, 2023)
Introduction: Individuals with schizophrenia spectrum disorders (SSDs) record elevated rates of smoking, which is often attributed to their effort to self-medicate cognitive and attentional symptoms of their illness. Empirical evidence for this hypothesis is conflicting, however. In this study, we aimed to test predictions derived from the cognitive self-medication hypothesis. We predicted that cigarette smoking status and extent would predict the attentional performance of participants with SSDs. Simultaneously, we wished to address methodological gaps in previous research. We measured distinct attentional components and made adjustments for the effects of other, attention-modulation variables. Methods: Sixty-one smokers (82.0% males, 26.73 ± 6.05 years) and 61 non-smokers (50.8% males, 27.10 ± 7.90 years) with recent-onset SSDs completed an X-type Continuous Performance Test, which was used to derive impulsivity and inattention component scores. Relationships between the two component scores and cigarette smoking status and extent were assessed using hierarchical regression. Effects of estimated premorbid intellectual functioning and antipsychotic medication dosage were held constant. Results: Smokers had significantly higher inattention component scores than non-smokers when covariates were controlled (p = .026). Impulsivity remained unaffected by smoking status (p = .971). Cigarette smoking extent, i.e., the number of cigarettes smoked per day, was not associated with either inattention (p = .414) or impulsivity (p = .079). Conclusions: Models of smoking-related attentional changes can benefit from the inclusion of sample-specific component scores and attention-modulating covariates. Under these conditions, smokers with SSDs can show a partial attentional benefit. However, the limited scope of this benefit suggests that the cognitive self-medication hypothesis requires further testing or reconsidering.